2012
DOI: 10.1103/physrevlett.108.074802
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Orbital Angular Momentum Transfer and Magnetic Dichroism in the Interaction of Electron Vortices with Matter

Abstract: Following the very recent experimental realization of electron vortices, we consider their interaction with matter, in particular, the transfer of orbital angular momentum in the context of electron energy-loss spectroscopy, and the recently observed dichroism in thin film magnetized iron samples. We show here that orbital angular momentum exchange does indeed occur between electron vortices and the internal electronic-type motion, as well as center-of-mass motion of atoms in the electric dipole approximation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 17 publications
2
67
0
Order By: Relevance
“…Electric and magnetic field effects provide a promising avenue for the shaping of electron beams. Electron beams' magnetic field sensitivity might also be exploited for magnetic field sensing in materials science 60 . Further still, recent work has proposed the potential application of structured electron beams to the selective excitation of atomic states, via a transfer of intrinsic electron OAM to electrons in individual atoms 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Electric and magnetic field effects provide a promising avenue for the shaping of electron beams. Electron beams' magnetic field sensitivity might also be exploited for magnetic field sensing in materials science 60 . Further still, recent work has proposed the potential application of structured electron beams to the selective excitation of atomic states, via a transfer of intrinsic electron OAM to electrons in individual atoms 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike photon OAM, electron OAM can directly excite dipole transitions in atoms through the Coulomb interaction. Not only can this lead to new selection rules in electron-atom interactions, but it can also be used for magnetic dichroism at atomic length scales [205][206][207][208][209]. Structured electrons have also recently been used to enhance phase contrast intransmission electron microscopy (TEM), providing the ability to image electron-transparent objects at small beam doses and improved spatial resolution [210].…”
Section: Statusmentioning
confidence: 99%
“…Since they were first reported, it has been suggested that electron vortex beams may be combined with the atomic resolution microscope probes to enable chiral spectroscopy with atomic resolution (Idrobo and Pennycook, 2011;Lloyd et al, 2012c;Rusz and Bhowmick, 2013;Verbeeck et al, 2011aVerbeeck et al, , 2010Yuan et al, 2013). However, there is currently some debate as to the conditions under which such high resolution will be achievable, and the limits of application of the vortex beam (Pohl et al, 2015).…”
Section: The E↵ect Of O↵-axis Vortex Beam Excitationmentioning
confidence: 99%